Do Bank Mergers has Forgone or Undergone Value? From the Perspective of Investor - Thapa, Neeta (The International Research Journal of Management Science, 2023)
Purpose: The purpose of the study is to explore banking industries investors’ perceptions about merged banks synergies “economies of scale, brand scope and market power “reaction to mergers. Design/methodology/approach: Based on the descriptive research design, a quantitative survey was adopted and administered to 117 investors through judgmental sampling techniques. Structural Equation Modeling (SEM) was then utilized to evaluate the significance of direct and indirect relationships between the various factors under study. Findings: The results confirm that the bank products & services and prices affect positively similarly, brand strategy and sales channels affects positively to the perceived gain of investors after mergers. Research limitations/implications: The absence of a longitudinal study measuring the post merger perception of investor is the main limitation of this study. Moreover, despite being insightful, the result of this study is generalized around small geographic area only. Originality/value: This study is an initial attempt to fill the void in published information about the behavioral finance of bank mergers. It provides new empirical insights about the effect of post-merger performance perceived by investor’s perspective.